The Effect of Competency Human Resources, Work Motivation, and Work Spirit on Employees Performance at the Service Cooperative & Msmes West Sumatra - M, Agussalim; Gema Motherland, Ega; Yanti, Novi (Dinasti International Journal of Digital Business Management, 2023)
This study aims to examine and see: 1) The influence of human resource competence partially on the performance of employees at the Office of Cooperatives and SMEs of West Sumatra Province . 2) The effect of work motivation partially on employee performance at the Office of Cooperatives and UMKM West Sumatra Province . 3) The partial effect of work enthusiasm on employee performance at the Office of Cooperatives and UMKM West Sumatra Province . 4) The simultaneous influence of HR competence, work motivation, and work spirit on employee performance at the Office of Cooperatives and UMKM West Sumatra Province . This type of research is quantitative The population in this study were 65 employees of the Office of Cooperatives and UMKM West Sumatra province. The sample uses a total sampling technique with a total of 65 employees. Sources of data in this study are primary data obtained from observations and questionnaires. The data analysis method used multiple linear regression, coefficient of determination, and t and f tests. The results show 1) Human resource competence partially has a positive and significant effect on the performance of the employees of the West Sumatra Province Cooperative and MSME Office . 2) Work motivation partially has a positive and significant effect on the employee performance of the Office of Cooperatives and UMKM West Sumatra Province . 3) Work morale partially has a positive and significant effect on the performance of the employees of the West Sumatra Province Cooperative and UMKM Service .. 4) HR competence, work motivation, and work spirit simultaneously affect the performance of the employees of the Cooperative Service andUMKM West Sumatra Province . The contribution level of influence of human resources competence, work motivation, and work spirit on the performance of the Office of Cooperatives and UMKM West Sumatra Province is 79.5%, while the remaining 20.5% is influenced by other variables not examined in this study, such as work discipline, job satisfaction, work behavior, work environment, and so on.